Influence of the use of gum Arabic or OSA starch and the drying process on the quality of the fava bean (Vicia faba) pod flour - María del Mar Camacho; Narcisa Fernández-Vargas; Eva García-Martínez; Nuria Martínez-Navarrete (Food Hydrocolloids for Health)
In the search for new foods that allow for healthy and sustainable eating, this study focuses on obtaining a flour from fava bean pods for consumption as a food ingredient. The influence of the drying process applied, hot air drying (AD) or freeze-drying (FD), and the incorporation of gum Arabic (GA) or sodium octenyl succinate starch (OSA) as potential carriers and encapsulant agents, on the composition, antioxidant activity and on some techno-functional properties of the powder was compared. In addition to the high starch and fiber content of the fava bean pod, GA increases the fiber soluble fraction, while OSA did so with starch. GA also provides minerals. On the other hand, the solid rather than viscous character of the films GA forms on the surface of the particles, unlike OSA, contributes to stabilize the compounds inside. FD keeps the product at a lower temperature during drying and involves obtaining a more porous structure that AD. However, the high phenol content of the bean pod, much higher than that of vitamin C and chlorophyll (mean values 40.8, 1.8 and 0.7 mg/g db, respectively), and the significant interaction between the hydrocolloids and drying process allows us to recommend the use of GA and AD to obtain a more economical powdered ingredient, healthier, and of the highest quality. These flours, in addition to having the highest phenol content and the highest antioxidant capacity, have the largest particle size and lowest porosity, which improves fluidity, hygroscopicity, wettability and solubility.